The influence of artificial saliva on the cleaning force of interdental rubber picks: an in-vitro comparison - Christian Graetz; Ann-Kristin Härdter; Susanne Schorr; Miriam Cyris; Antje Geiken; Thomas Rinder; Christof E. Dörfer; Sonja Sälzer (BMC, 2022)
Abstract Background The familiar aids for interdental cleaning such as dental floss or interdental brushes (IDB) are often associated with difficult handling or an increased potential for trauma. Interdental picks (IRP), which have no metal core and silicone flaps instead of nylon brushes, offer the alternative. However, in-vitro studies found a lower cleaning effectiveness combined with higher forces for cleaning compared with conventional IDBs. The aim of this in-vitro study was to measure the experimental cleaning forces (ECF) using IRP with versus without an artificial saliva (AS; GUM Hydral, Sunstar Suisse SA, Etoy, Switzerland). Methods The test set-up was developed to investigate the cleaning of 3D-printed interdental area (IDR) mimicking human teeth (Form 2, Formlabs Sommerville, MA, USA) under standardized conditions. Three different morphologies (isosceles triangle, convex, concave) and three different sizes (1.0 mm,1.1 mm,1.3 mm) were used. Two different IRPs (GUM Soft-picks Advanced: SPA versus GUM Soft-picks Advanced Plus: SPA+, Sunstar Suisse SA, Etoy, Switzerland) in three sizes (small, regular, large), were used with versus without AS. ECF during ten cleaning cycles were recorded by a load cell [N]. Results Using AS leaded to significant lower values for ECF than without (1.04 ± 0.66 N versus 1.97 ± 1.01 N, p < 0.001). In general, a lower ECF was recorded for convex IDR compared to isosceles triangle and concave morphologies (p < 0.001) as well as for gap sizes of 1.3 mm compared to the smaller sizes (p < 0.001). For SPA+ we found significantly higher force values than for SPA (1.67 ± 0.93 N versus 1.31 ± 0.97 N, p < 0.001) independent of the use of AS. Conclusion Within the study´s in-vitro limitations, we found AS reduced ECF of IRPs by half and allowed using larger diameters interdentally, which could be associated with (1) a higher cleaning effectiveness and (2) a higher acceptance e.g. of patients with dry mouth. This has to be confirmed by further clinical investigations.